Pendidikan Anti Korupsi dan Gerakan Anti Politik Uang Bagi Generasi Z Sebagai Pemilih Pemula Untuk Mewujudkan Pemilu Serentak Tahun 2024 Yang Berintegritas - Daulat Nathanael Banjarnahor; Firinta Togatorop (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The community service program in this article provides outreach to new voters about Anti-Corruption Education and the Anti-Money Politics Movement, ahead of the 2024 General Election. Anti-Corruption Education is an action to control and reduce corruption in the form of an effort to encourage future generations to develop a firm attitude towards every form corruption. Money politics is a form of giving or promising to bribe someone either so that the person does not exercise their right to vote or so that they exercise their right in a certain way during the general election. Political education is a form of political outreach to the public to understand and understand politics, especially to the general public regarding general elections and the democratic process therein. Political education also contains the meaning of political participation, meaning that society also participates in the political process. The choice of the GKPI 2 Pematangsiantar Private Vocational School was due to the high level of first-time voters in the 2024 elections, so the team felt it was necessary to provide socialization about political education to many young voters who were in high school. We want GKPI 2 Pematangsiantar Private Vocational School students to be aware and have adequate knowledge regarding preparations for the upcoming 2024 elections. The output target that we hope for as organizers and cooperation partners is the understanding of GKPI 2 Pematangsiantar Private Vocational School students which can be obtained from the political education regarding preparation for the 2024 Election that we provide. By participating in this socialization, it is hoped that students will be able to provide an understanding of the material presented to their peers or people outside the school environment. Participants in our community service activities are representatives from each class at the GKPI 2 Pematangsiantar Private Vocational School who are 17 years of age or older, or who will have the right to vote when the elections are held